Detection of Subsurface Cavities by Using Pole- Dipole Array (Bristow's Method)/Hit Area-Western Iraq - Thabit, Jassim; Abed, Ali (Iraqi Journal of Science, 2023)
The study area is located within the Hit area, western Iraq. The measurements of Graphical Bristow’s method were carried out by using Pole-dipole array, to delineate the anomaly of apparent resistivity caused by a known cavity target. The survey was applied along two traverses: traverse in W-E direction and traverse in S-N direction above Um El-Githoaa cavity. Data interpretation of the traverse trending W-E, with a-spacing equal to(2m)identified the anomaly of the cavity at a depth of (2.6m), (1.6m) height, and( 9.5m) width, while the actual dimensions of depth, height, and width were (3.80m),( 2.2m), and (12.30m) respectively, with variations of depth equal to (1.2m), high (0.8m), and width( 2.8m). The data interpretation with a-spacing of (3m) over the same travers W-E identified small differences from actual dimensions of the cavity, which are approximately equal to (0.4m), (0.6m), and (1m) for depth, height, and width respectively. This means that the survey by using (a=3m) identified a very accurate detection and location of this cave; more than the survey of (a=2m).Therefore, the survey along the traverse S-N is also performed with (a=3m). The data interpretation indicated that the cavity of depth, height, and width are (3.3m),( 2.20m), and(18.6m) respectively, which are approximately the same as the actual dimensions of the cavity with small variations of about (0.5m) depth, (0.4m) high, and (1m) width. It is concluded that the a-spacing is a very important factor, because of its effect on the accurate determinations of subsurface cavity. So, it must be taken into consideration in choosing a-spacing in the filed before taking the measurements by using Bristow's method.